Evaluation of the influence of mandibular third molars on mandibular anterior crowding relapse. (18th May 2020) - Cotrin, Paula; Freitas, Karina Maria Salvatore; Freitas, Marcos Roberto; Valarelli, Fabrício Pinelli; Cançado, Rodrigo Hermont; Janson, Guilherme
Abstract: Objective: To evaluate the influence of mandibular third molars on relapse of mandibular anterior crowding in orthodontically treated patients. Material and Methods: Sample included orthodontic records of 108 patients: Group 1: 72 patients (39 female; 33 male) with third molars present in the postretention evaluation stage. Group 2: 36 patients (18 female; 18 male) who did not present the third molars in the postretention evaluation stage. Panoramic radiographs and dental models were evaluated at three different stages: pre-treatment; posttreatment and postretention. Panoramic radiographs showed the presence or absence of third molars in the 3 evaluated stages and on the dental models, overbite and mandibular anterior crowding was measured by the Little Irregularity Index. For intergroup comparisons, t -tests and a multifactorial regression analysis were used. Results: There was no statistically significant difference in the relapse of mandibular anterior crowding among the groups with and without mandibular third molars at the postretention stage. Conclusion: The presence or absence of mandibular third molars did not influence the relapse of mandibular anterior crowding in orthodontically treated patients.